(untitled) (International journal of artificial intelligence, 2025)
The chemical composition of phosphogypsum was determined by X-ray analysis and calculation, which consists mainly of CaSO4·2H2O, CaSO4∙H2O, CaCO3, CaCl3 b CaF2, as well as MgSO4∙Н2О and other compounds.